Experimental investigation of beam-ion losses induced by magnetic perturbations using the light ion beam probe technique in the ASDEX Upgrade tokamak. (1st September 2022) - Galdon-Quiroga, J.; Sanchis-Sanchez, L.; Chen, X.; Birkenmeier, G.; Gage, K.; Cano-Megias, P.; Gonzalez-Martin, J.; Heidbrink, W.W.; Putignano, O.; Ryan, D.; Suarez Lopez, G.; Tal, B.; et al.
Abstract: The impact of externally applied magnetic perturbations (MPs) on fast-ion losses has been investigated by means of the light ion beam probe (LIBP) technique in the ASDEX Upgrade tokamak. The LIBP technique allows to experimentally infer the fast-ion orbit displacement induced by MPs via first-orbit losses using scintillator based fast-ion loss detector (FILD) measurements. The fast-ion orbit displacement against different applied MP spectra has been studied. These shots were conducted in ELM mitigated H-mode plasmas. A rigid rotation of the MP coils was applied with a frequency of 1 Hz, with an n = 2 configuration and changing the differential phase between the upper and lower set of coils (ΔΦul ) on a shot-to-shot basis. Beam sources Q7 (tangential) and Q8 (radial) were used to probe different fast-ion orbits with FILD1. The measured fast-ion orbit displacement ranges from 3 to 20 mm approximately, and no qualitative difference is observed between ions from beam sources Q7 and Q8. The minimum is found for a ΔΦul ∼ 50°, which is shifted with respect to the minimum of the plasma boundary displacement, found at ΔΦul ∼ 0°. A first attempt to validate the orbit following code ASCOT—including the plasma response calculated with the MARS-F code—against these experimental measurements is performed. While the dependence of the first-orbit fast-ion displacement with ΔΦul does not match the experimental measurements, these simulations do capture other features such as the order of magnitude of the orbit displacement and the importance of the toroidal spectrum of the applied perturbation.